Islington Miners Support Committee, 1984 (London, 1984)
1984 1980-95 "Islington Miners Support Committee, 1984" [BW0095], 1984, Trades Union Congress In March 1984, when the National Coal Board announced the closure of five pits without proper review, miners in Yorkshire and Scotland started official strike action. These were endorsed by the National Union of Mineworkers (NUM) executive which called on other areas to support them. The Conservative Government under Margaret Thatcher brought the full weight of the law down on the striking miners and the NUM's funds were seized on October 24, 1984 by order of the High Court. Several hundred miners were dismissed and never taken back. Miners were denied state benefits and the police were mobilised to deal with picket lines on the grounds that they represented illegal public disturbances. A huge support network sprang up across the country, as shown in this leaflet issued by the Support Committee in Islington, London. The strike ended on March 3, 1985, nearly a year after it had begun, when the NUM conceded defeat.